High-resolution multiscale modeling of mechanical behavior of cold-drawn pearlitic steels - Xutao Huang (Elsevier, 2021)
A strategy based on representative volume element (RVE) was proposed to investigate the mechanical behavior of cold-drawn pearlitic steels at multiscale. Firstly, a finite element model based on macroscale was used to simulate the cold drawing. The partial mesh of the model was refined to obtain a RVE-scale element, and the elastic-plastic strain of this element were extracted and mapped to the RVE model. For further research, a high-resolution RVE model based on the crystal plasticity finite element method (CPFEM) was established to investigate the mechanical behavior of the pearlite. In addition, a new method of hierarchical partition was used for geometric modeling. Crucially, the simulated pole figures were in high agreement with the experimental results, both prominently showing an α-fiber texture. The final results indicated that the plasticity and strength of the pearlitic steels were determined by the coordinated deformation between pearlite nodules and the interaction between ferrite and cementite.